2003
DOI: 10.1038/sj.bmt.1704365
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell donor registry strategies for assigning search determinants and matching relationships

Abstract: Summary:Registries and cord blood banks around the world collect and store the HLA types of volunteers in order to identify matched unrelated donors for patients requiring hematopoietic stem cell transplantation. This task is complicated by the many formats in which HLA types are provided by the testing laboratories (types obtained by serology vs by DNA-based methods; high vs intermediate vs low resolution) and by the need to identify which of these diverse types are most likely to match the HLA assignments of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…18,19 For comparison and analysis of CREG matching, the high-resolution HLA data were converted to serologic equivalents. 20,21 The extents of allele matching for study populations are described in Tables 2-3.…”
Section: Hla Assignmentsmentioning
confidence: 99%
“…18,19 For comparison and analysis of CREG matching, the high-resolution HLA data were converted to serologic equivalents. 20,21 The extents of allele matching for study populations are described in Tables 2-3.…”
Section: Hla Assignmentsmentioning
confidence: 99%
“…Searching algorithms aim at finding the optimal match between the patient and the potential donor. 2 As the '10/10 matched' (that is, high-resolution identity at loci HLA-A, -B, -C, -DRB1 and -DQB1) donor is not always available, some extent of HLA mismatch (Mm) can be accepted; however, there is still some controversy about the precise impact of HLA mismatching on HSCT outcomes, because published reports indicate discordant results about the relative importance of loci involved. [3][4][5][6][7][8][9][10][11][12][13][14] A recent study by Lee et al 3 indicated that both class I and class II Mms affect survival, suggesting that each HLA Mm is associated with an additional unadjusted survival impairment of 9-10%.…”
Section: Introductionmentioning
confidence: 99%
“…These guidelines are firmly based on the nomenclature developed by the World Health Organization Nomenclature Committee for Factors of the HLA System 14 and uniformly accepted by the HLA community and on the requirements for presenting and condensing HLA data within the format of the registries' information systems. 8 A strategy for the latter has been in use for a long time, but neither specified nor standardized so far. Table 1 describes reference web sites that include relevant information for these guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Continuously updated lists of assignments and correspondences approved in the context of these guidelines will be maintained on two WMDA-specified reference web sites: the IMGT/HLA database for HLA nomenclature (www.anthonynolan.org.uk/HIG/nomen/wmda.html) 15 and the US National Marrow Donor Program web site for codes that include multiple allele alternatives (bioinformatics. nmdp.org/HLA/allele_codes_idx.html) 8 (Table 1). The latter site includes contact information for registry requests for 2.3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation